India's policy and programmatic response to mental health of young people: A narrative review - Bhushan Girase; Rachana Parikh; Samica Vashisht; Anushka Mullick; Vaibhao Ambhore; Sudhir Maknikar (Elsevier, 2022)
India's response to meet the mental health needs of 252 million young people between 15 and 24 years is guided by the Mental Healthcare Act 2017 (MHCA), which advocates a rights-based approach to receiving mental healthcare, the National Mental Health Policy 2014, and the National Mental Health Program operational since 1982.We undertook a comprehensive narrative review of policies, programs, and legislations across five ministries of the Government of India-Health and Family Welfare, Education, Women and Child Development, Youth Affairs and Sports, and Social Justice and Empowerment-over the last ten years to map their approach and identify enablers and barriers for promoting youth mental health in India. Our work builds on the previous reviews on children and adolescents' mental health in India and captures the rapidly advancing policy landscape amidst the new challenges and opportunities presented by the COVID-19 pandemic, especially the increasing acceptability of digital health interventions including tele-consultations.We note that all the five ministries recognized mental health as an important aspect of overall development and well-being of young people. However, their approach is fragmented and a comprehensive approach to youth mental health is missing in the Indian context. Having said that, many enablers for integration of preventive, promotive, and curative mental health interventions exist especially as mental health is increasingly being recognized as an integral part of the comprehensive primary healthcare. However, much needs to be done in terms of strategic planning for screening, early detection and treatment, and developing strong referral systems between community, schools and mental healthcare services. Effective implementation of MHCA, sustainable intersectoral integration of mental health across youth-oriented services, empowerment of young people, and judicious use of digital technology hold the key to reimagining the approach to advance young people's mental health in India.